Islamic Marketers Multipurpose Products In Increasing Islamic Bank Customers - Dimas Ramadhani (LPPM ISNJ Bengkalis, 2023)
One thing that differentiates Islamic marketers from conventional marketers is their muamalah, namely, referring to Islamic law principles. This research aims to analyze the implementation of Islamic marketers in increasing the number of multipurpose product customers at the office channelling of Bank Sumsel Babel Pangkalpinang Syariah Branch. This research is a type of case study research with a qualitative approach. The data sources used are primary and secondary. Data collection techniques use interviews, observation, and literature. The results of the research show that the implementation of Islamic marketers includes Theistic (rabbaniyyah) implemented because the appearance of Islamic marketers is closed, covering the private parts and wearing the hijab; Ethical (akhlaqiah) implementation always behaves well, speaks politely, and not differentiate between one customer and another; Realistic (waqiyyah), namely the officer is honest in offering the product and does not exaggerate the product's advantages; Humanism (insaniyyah) implemented because officers always respect customers who come and are friendly regardless of ethnicity, religion, and race. The results of this research can be a reference for Islamic banking or other Islamic financial institutions to implement Islamic marketers in marketing products to the public.